Addressing the burden of cervical cancer for Indigenous women in Latin America and the Caribbean: a call for action - Claire Muslin (Frontiers Media S.A., 2024)
Cervical cancer, primarily caused by human papillomavirus (HPV) infection, poses a significant global health challenge. Due to higher levels of poverty and health inequities, Indigenous women worldwide are more vulnerable to cervical cancer than their non-Indigenous counterparts. However, despite constituting nearly 10% of the population in Latin America and the Caribbean (LAC), the true extent of the burden of cervical cancer among Indigenous people in this region remains largely unknown. This article reviews the available information on cervical cancer incidence and mortality, as well as HPV infection prevalence, among Indigenous women in LAC. The limited existing data suggest that Indigenous women in this region face a heightened risk of cervical cancer incidence and mortality compared to non-Indigenous women. Nevertheless, a substantial knowledge gap persists that must be addressed to comprehensively assess the burden of cervical cancer among Indigenous populations, especially through enhancing cancer surveillance across LAC countries. Numerous structural, social and cultural barriers hindering Indigenous women's access to HPV vaccination and cervical cancer screening worldwide have been identified and are reviewed in this article. The discussion highlights the critical role of culturally sensitive education, community engagement, and empowerment strategies in overcoming those barriers. Drawing insights from the success of targeted strategies in certain high-income countries, the present article advocates for research, policies and healthcare interventions tailored to the unique context of LAC countries.